경쟁 / 협동상황에서의 4 - 5세 아동의 상호작용 관찰 연구 - 김판희(Pan Hee Kim) (Korean Journal of child studies, 1996)
The purpose of the present study was to investigate how 4-to 5-year-olds approach a competitive/cooperative task to obtain a resource. Sex and age differences were examined for the behavior and resource utilization of this task. The subjects were 74 same-age, mixed sex groups of 4 children each in three kindergartens in a large city. Each group of 4 children were classmates. The children were videotaped in a play situation where one child could view a cartoon movie (i. e. acquiring a resource) with the assistance of two children (one to turn the film tape and one to push the light-button), and the fourth child was a bystander. Time at each position and physical and verbal behavior constitute the data which were analyzed by ANOVA and ${χ}^2$. The results of the time analysis showed that children cooperated quickly and were able to view the cartoon(resource utilization) for a large part of the session. High resource utilizers compared with low resource utilizers, exhibited more self-assertive and helping behaviors. Boys achieved more viewing time while girls were bystanders for a greater amount of time. Boys showed more physical and verbal behaviors during the task. Four-year-olds achieved less viewing time than 5-year-olds, indicating 4-year-olds were less effective in eliciting the help of their peers.